2022
DOI: 10.2147/rmhp.s354758
|View full text |Cite
|
Sign up to set email alerts
|

How Efficient are Basic Public Health Services Between Urban and Rural in Shandong Province, China? A Data Envelopment Analysis and Panel Tobit Regression Approach

Abstract: Background Improving basic public health services efficiency becomes priority to guarantee its sustainability for Chinese government. This study aimed to explore basic public health services efficiency and its influencing factors between urban and rural in Shandong Province, China, providing policy implications to improve efficiency. Methods This research assessed basic public health services efficiency of 54 districts (representing urban) and 83 counties (representing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 11 publications
0
15
1
Order By: Relevance
“…Therefore, social conflicts are concentrated in more populated areas, and the government will face further challenges and difficulties in providing various livelihood services. (3) Regional GDP is a proxy for the level of economic development of a region, and the regression finds that the level of economic development in each region has a certain hindering effect on the efficiency of livelihood improvement, which is inconsistent with the findings of most studies [7,38,56]. On the one hand, this is because higher levels of economic development weaken the government's efforts in cost control, resulting in lower efficiency.…”
Section: Discussion Of Regression Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…Therefore, social conflicts are concentrated in more populated areas, and the government will face further challenges and difficulties in providing various livelihood services. (3) Regional GDP is a proxy for the level of economic development of a region, and the regression finds that the level of economic development in each region has a certain hindering effect on the efficiency of livelihood improvement, which is inconsistent with the findings of most studies [7,38,56]. On the one hand, this is because higher levels of economic development weaken the government's efforts in cost control, resulting in lower efficiency.…”
Section: Discussion Of Regression Resultsmentioning
confidence: 92%
“…For example, Lin et al emphasise that population size and population structure can be important influencing factors but do not provide further evidence on their specific impact [55]. Cao et al found empirically that the total population of a region was negatively associated with the efficiency of health services [56]. Khan et al argue that this negative correlation is mainly because, as the population size of a region increases, it negatively affects the equity and fairness of public services, and, by extension, service efficiency [57].…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations